English Language Target Needs Of Medical Students At Ibb University In Yemen - Hussein Farea, Wafa Ahmed Ali (2023)
Driven by the understanding that learners’ needs should be considered for an effective English for Specific Purposes (ESP) course, this study aimed to investigate the English language target needs for the development of the existing ESP course at the Faculty of Medicine and Health Sciences (FMHS) at Ibb University (IU) in Yemen. The needs analysis (NA) is a vital asset in designing and developing suitable ESP curriculum to meet the academic and professional requirements of the students. The conceptual framework of the present study is based on structuration theory and constructivism theory, along with Hutchinson and Waters’ (1987) framework utilised as a tool to identify the learners’ necessities, lacks and wants. A triangulation research method was followed in the present study. Thus, two different instruments, questionnaires and semi-structured interviews were used to collect quantitative and qualitative data. A sequential explanatory mixed-methods approach was adopted for the English language target needs analysis. The maximum variation purposive sampling strategy, the most common purposive sampling strategy, is employed in the current study to select a representative sampling of the stakeholders and to give much insight into needs analysis from different perspectives.